Research on the Path of Green Economic Transformation and Technological Innovation Policy from the Perspective of Corporate Social Responsibility - Feng, Simin (International Journal of Social Sciences and Public Administration, 2025)
Driven by global climate governance and sustainable development goals, corporate social responsibility (CSR) is shifting from passive compliance to proactive innovation, becoming the core engine of green economy transformation. Based on CSR perspective, this study explores the synergy path between technological innovation policy and green economy transformation. By analyzing the mechanism of incentive and constraint policies and international practical experience, this paper reveals the efficiency boundary of policy tools in driving enterprise technological innovation, and puts forward the transformation path of "technology-institution-governance" linkage. The results show that CSR internalizes social responsibility into technological innovation power by reshaping enterprise cost-benefit structure; policy design needs to balance hardness and softness, and stimulate enterprise endogenous transformation willingness through incentive and constraint combination tools; the success of green economy transformation depends on the deep coordination among government, enterprise and society in standard setting, resource sharing and benefit coordination.